Early development of the Patagonian fold and thrust belt and the onset of foreland sedimentation in the Austral-Magallanes basin - Naipauer, Maximiliano (2024)
Retroarc basins register the onset of compressional exhumation during the Cretaceous in the Andes, evidenced by sequences showing sedimentary provenance from the orogen. We present U–Pb detrital zircon geochronology from the Austral-Magallanes basin in the Southern Patagonian Andes (∼47–48°SL), where the foreland stage began in the Early Cretaceous. The littoral sandstones from basal foreland sequences of the Río Belgrano Formation yield ∼123 Ma maximum depositional ages, confirming previous studies that the basin infill is early Aptian. The detrital zircon ages showed two main clusters of 129-115 Ma and 151 -140 Ma, that are derived from the coetaneously exhumed Andean arc and earlier Jurassic magmatic sources. The zircons which overlap with ages of Upper Jurassic Andean synrift volcanics, confirms orogenic exhumation coeval with sedimentation. A sequence of retroarc volcanism dated between 119 and 97 Ma overlies the basal foreland littoral-continental deposits, and it is followed by a Late Cretaceous-Paleocene hiatus. Further analysis of detrital zircons ages distribution and geological considerations, indicates that the studied northern depocenter was a source region of sedimentary supply after its Cenomanian exhumation.